2021
DOI: 10.1016/j.cmi.2021.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical significance of relative bradycardia at hospital admission in patients with coronavirus disease 2019 (COVID-19)

Abstract: Heart rhythm disorders are increasingly reported during coronavirus virus disease 2019 and the presence of relative bradycardia (RB), known as an inappropriate low heart rate (HR) in response to an increased body temperature (BT), has been reported only occasionally [1]. However, its definition varied widely among studies and little is known regarding its role in predicting clinical outcomes [1,2]. We evaluated the prevalence and clinical significance of RB at hospital admission in patients with COVID-19. Fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 5 publications
2
19
0
Order By: Relevance
“…Vascular inflammation and endothelial activation have been related to the spectrum of COVID-19-associated coagulopathy [5]. Furthermore, among others, the role of sE-selectin as a marker of endothelial dysfunction, inflammation or damage, points out the central role of the endothelium itself not only in the development of a more severe form of the disease, but also in the pathogenesis of the cardiovascular events that occur during COVID-19, including immuno-thrombosis and arrhythmias [6]. As a matter of fact, the inflammatory milieu as a consequence of the so-called 'cytokine storm' may contribute to the progression of endothelial damage, which, in turn, amplifies the pro-inflammatory and pro-coagulant processes [21] as well as the high production of reactive oxygen species [18], all conditions observed during severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular inflammation and endothelial activation have been related to the spectrum of COVID-19-associated coagulopathy [5]. Furthermore, among others, the role of sE-selectin as a marker of endothelial dysfunction, inflammation or damage, points out the central role of the endothelium itself not only in the development of a more severe form of the disease, but also in the pathogenesis of the cardiovascular events that occur during COVID-19, including immuno-thrombosis and arrhythmias [6]. As a matter of fact, the inflammatory milieu as a consequence of the so-called 'cytokine storm' may contribute to the progression of endothelial damage, which, in turn, amplifies the pro-inflammatory and pro-coagulant processes [21] as well as the high production of reactive oxygen species [18], all conditions observed during severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 can result in a spectrum of forms ranging from a respiratory tract infection to a systemic and severe form characterized by acute respiratory distress syndrome, shock and thrombotic events [2][3][4]. A great number of these phenomena have been investigated and considerable attention has been paid to the vascular manifestations of the disease [5,6]. Multiple studies have illustrated SARS-CoV-2 to target epithelial cells causing local inflammation leading to an imbalance between anti-coagulant and pro-thrombotic factors [7].…”
Section: Introductionmentioning
confidence: 99%
“…An unusual feature that is sometimes seen in patients diagnosed with COVID-19 is the appearance of bradycardia, i.e. slow heart rate, or heart rate not increasing as expected with body temperature 11–14 . Amaratunga et al 15 found bradycardia in a study of 4 patients with confirmed COVID-19, with minimum pulse rates in the range 42−49 beats per minute.…”
Section: Introductionmentioning
confidence: 95%
“…Cardiac complications are known to be associated with the COVID-19 disease caused by the novel Severe Acute Respiratory Syndrome—Coronavirus 2 (SARS-CoV-2) ( Cizgici et al, 2020 ; Huang et al, 2020 ; Kochi et al, 2020 ; Long et al, 2020 ; Shi et al, 2020 ; Siripanthong et al, 2020 ; Wang et al, 2020 ; Coromilas et al, 2021 ). An unusual feature that is sometimes seen in patients diagnosed with COVID-19 is the appearance of bradycardia, i.e., slow heart rate, or heart rate not increasing as expected with body temperature ( Ikeuchi et al, 2020 ; Capoferri et al, 2021 ; Douedi et al, 2021 ; Oliva et al, 2021 ). Amaratunga et al (2020) found bradycardia in a study of 4 patients with confirmed COVID-19, with minimum pulse rates in the range 42–49 beats per minute.…”
Section: Introductionmentioning
confidence: 96%